Molecular Dissection of CD8+ T-Cell Dysfunction. Issue 8 (August 2017) - Wang, Chao; Singer, Meromit; Anderson, Ana C.
Abstract : Chronic viral infections and cancer often lead to the emergence of dysfunctional or 'exhausted' CD8 + T cells, and the restoration of their functions is currently the focus of therapeutic interventions. In this review, we detail recent advances in the annotation of the gene modules and the epigenetic landscape associated with T-cell dysfunction. Together with analysis of single-cell transcriptomes, these findings have enabled a deeper and more precise understanding of the transcriptional mechanisms that induce and maintain the dysfunctional state and highlight the heterogeneity of CD8 + T-cell phenotypes present in chronically inflamed tissue. We discuss the relevance of these findings for understanding the transcriptional and spatial regulation of dysfunctional T cells and for the design of therapeutics. Trends: Recent advances have identified novel CD8 + T-cell functional states in chronic inflammatory conditions associated with distinct transcriptional programs. Single-cell analysis has revealed extensive transcriptional heterogeneity in the CD8 + T-cell response in cancer. CRISPR/Cas9 genome editing in mature CD8 + T cells has enabled testing of candidate regulators in vivo . Analysis of the chromatin landscape in CD8 + T cells has revealed distinct epigenetic changes associated with distinct functional states.